2021
DOI: 10.1111/1750-3841.15986
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of genetic divergence of coffee genotypes using the volatile compounds and sensory attributes profile

Abstract: The quality of the coffee beverage is related to the chemical, physical, and sensory attributes of the coffee beans that vary with the geographic location of the crop, genetic factors, and post-harvest processing. So, the objective of this study was to evaluate the genetic divergence of 27 genotypes of Coffea canephora using the volatile compounds and sensory attributes profile to select genotypes that produce a coffee beverage with high sensory quality. This genetic diversity was estimated from the Euclidean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 37 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…La calidad en la bebida de café es el resultado de factores y condiciones del suelo (Veloso et al, 2020), altitud (Tolessa et al, 2017), genética (Machado et al, 2022), sombra (Torrez et al, 2023), manejo agronómico (Cabrera-Rodríguez et al, 2020;Jurburg et al, 2020), plagas y/o enfermedades (Echeverria-Beirute et al, 2018). Por ejemplo, en el cultivo de café arábica, altitudes elevadas influye directamente en la composición química de los granos, así como el perfil microbiano y sensorial, en particular el aroma y fragancia (Martins et al, 2020).…”
Section: Microbioma Y Compuestos Asociados a La Calidad Del Caféunclassified
“…La calidad en la bebida de café es el resultado de factores y condiciones del suelo (Veloso et al, 2020), altitud (Tolessa et al, 2017), genética (Machado et al, 2022), sombra (Torrez et al, 2023), manejo agronómico (Cabrera-Rodríguez et al, 2020;Jurburg et al, 2020), plagas y/o enfermedades (Echeverria-Beirute et al, 2018). Por ejemplo, en el cultivo de café arábica, altitudes elevadas influye directamente en la composición química de los granos, así como el perfil microbiano y sensorial, en particular el aroma y fragancia (Martins et al, 2020).…”
Section: Microbioma Y Compuestos Asociados a La Calidad Del Caféunclassified
“…Furthermore, using the technique of single nucleotide polymorphisms of molecular markers, Alkimim et al(2018) showed higher genetic distance between groups of conilon and robusta (C. canephora) than among varieties within C. arabica species(Akpertey et al, 2022;Alkimim et al, 2018). In the case of C. canephora, allogamy and gametophytic self-incompatibility are responsible for the high heterogeneity and genetic variability of the species(Machado et al, 2022).…”
mentioning
confidence: 99%